Previously defined variants of uncertain significance may play an important role in epilepsy and interactions between certain variants may become pathogenic - Yara Hussein; Hila Weisblum‐Neuman; Bruria Ben Zeev; Shani Stern (Epilepsia Open)
Abstract Objective Epilepsy is a chronic neurological disorder related to various etiologies, and the prevalence of active epilepsy is estimated to be between 4 and 10 per 1000 individuals having a significant role in genetic mutations. Next‐Generation Sequencing (NGS) panels are utilized for genetic testing, but a substantial proportion of the results remain uncertain and are not considered directly causative of epilepsy. This study aimed to reevaluate pediatric patients diagnosed with epilepsy who underwent genetic investigation using NGS panels, focusing on inconclusive variant findings or multiple variants of uncertain significance (VUSs). Methods A subgroup of pediatric patients aged 0–25 years, diagnosed with epilepsy, who underwent genetic investigation with an NGS epilepsy panel at the Child Neurology Unit, The Edmond and Lily Safra Children's Hospital, Sheba Medical Center, between 2018 and 2022 through Invitae, was reevaluated. Patients with inconclusive variant findings or multiple VUSs in their test results were included. Genetic data were analyzed to identify potentially pathogenic variants and frequent genetic combinations. Results Two unrelated potentially pathogenic variants were identified in the SCN9A and QARS1 genes. A frequent genetic combination, RANBP2&RYR3, was also observed among other combinations. The RANBP2 gene consistently co‐occurred with RYR3 variants in uncertain results, suggesting potential pathogenicity. Analysis of unaffected parents' data revealed certain combinations inherited from different parents, suggesting specific gene combinations as possible risk factors for the disease. Significance This study highlights the importance of reevaluating genetic data from pediatric epilepsy patients with inconclusive variant findings or multiple VUSs. Identification of potentially pathogenic variants and frequent genetic combinations, such as RANBP2&RYR3, could aid in understanding the genetic basis of epilepsy and identifying potential hotspots. Plain Language Summary We have performed a retrospective analysis on a subpopulation of pediatric patients diagnosed with epilepsy. We found that specific genetic variants were repeatable, indicating their potential pathogenicity to the disease.